Employee at the Binjai City Regional Secretariat Office - Affandi, Andi; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The aim of this research is to determine and analyze the influence of Work Involvement on Work Competence at the Binjai City Regional Secretariat Office. This research was carried out at the Binjai City Regional Secretariat Office. The type of research is associative quantitative. The sample in this study was 24 employees with ASN and honorary status in the General Section of the Binjai City Regional Secretariat Office. The sampling technique in this research uses a saturated sample, where the entire population will be sampled in this research, 24 people. The research results show that Job Involvement has a significant influence on Job Competence as shown by the T-Statistic value of 3,605 > 1.710 and the P Value of 0.002 < 0.05. This shows that improvements in Work Engagement can increase Work Competence at the Binjai City Regional Secretariat Office. The results of the Adjusted R Square value show 0.228 or 22.80%, which means that Work Engagement has a low influence on employee Work Competence while the remaining 77.20% is influenced by other factors that have not been researched.